STATE REGULATION OF REALTOR ACTIVITY AT THE REAL ESTATE MARKET - S. Nuryiakhmetova (Russian Journal of Economics and Law)
The article views the problems of state regulation of realtor activity at the real estate market and shows their peculiarities. Special attention is given to revealing the main directions of realtor activity improvement in modern conditions.